Role of CD28+ PD-1+ Tc cells in immune response and prognosis prediction in hepatocellular carcinoma - Yang, Wuhan; Pan, Teng; Chen, Yaowen; Guo, Hao; Peng, Yaqi; Wang, Chao; Peng, Li; Wang, Shubin (Frontiers in Immunology, 2025)
BackgroundCD28+PD-1+ Tc cells (CD8+ T cells) constitute a dysfunctional subset of T cell; however, the mechanisms underlying their dysfunction and their significance in hepatocellular carcinoma (HCC) remain unclear. We aimed to elucidate the prognostic significance and molecular characteristics of CD28+PD-1+ Tc cell infiltration in HCC.MethodsWe established a single-cell HCC transcriptional map, focusing on cell-cell communication and trajectory analysis of CD28+PD-1+ Tc cells. We assessed the correlation between CD28+PD-1+ Tc-cell enrichment and prognosis and investigated potential molecular mechanisms using enrichment analyses. Flow cytometry was used to compare CD28+PD-1+ Tc-cell infiltration between HCC and adjacent normal tissues and cytotoxic factors and immune checkpoint expression were evaluated.ResultsOverall, 25,644 T cells were identified from single-cell RNA sequencing data from 10 HCC samples and corresponding normal samples. Overall T-cell infiltration was lower in HCC tissues, with significantly higher CD28+PD-1+ Tc-cell infiltration. Bulk RNA sequencing data integration revealed a correlation between higher CD28+PD-1+ Tc-cell infiltration and significantly worse prognosis. Flow cytometry confirmed higher CD28+PD-1+ Tc-cell enrichment in HCC tissues. Additionally, cytotoxic factor expression was significantly lower in CD28+PD-1+ Tc cells than in CD28-PD-1+ Tc cells, with lower expression of TIGIT and TIM-3 immune checkpoint molecules.ConclusionsSignificantly high CD28+PD-1+ Tc-cell enrichment in HCC indicates potential immune dysfunction. CD28+PD-1+ Tc-cell enrichment may serve as a sensitive prognostic marker and indicator for predicting treatment responses.